Algorithm of iterative transformation for effective modules of multicomponent isotropic composite; IOP Conference Series: Materials Science and Engineering; Vol. 177 : Mechanical Engineering, Automation and Control Systems (MEACS 2016) - Svetashkov A. A. Aleksandr Andreevich; Micinski J.; Pavlov M. S. Mikhail Sergeevich; Vakurov A. A. (Numerical simulation of applied problems, 2017)
Title screen